Effective perioperative scoring in orthopedic surgery to prevent Covid-19 infection - Irianto, Komang Agung; Adityawardhana, Taufan (Universa Medicina, 2021)
BackgroundThe pandemic has placed health-care workers (HCW) under an unprecedented strain where surgeries are being delayed and health care workers’ deaths because of COVID-19 are prominent and causing staff shortages. An effective, fast, and concise approach to preoperative screening is very much needed. Hospitals are suggested to develop their own algorithm to minimize delays and complications. The objective of this study was to optimize HCW safety by developing a working system based on the hospital’s service capability in treating orthopedic surgeries. Methods A retrospective study was conducted involving 305 HCW. Data were collected on the application of a novel elective and emergency orthopedic surgery clinical pathway and scoring method based on questionnaires, and laboratory and radiographic chest examinations for several months to ensure the safety of HCW. HCW COVID-19 status was routinely checked as the indicator of HCW’s safety. Results Mean age of all patients was 47.0 ± 22.41 years. The screening process was done in a series of questionnaires and laboratory examinations, with the majority of patients (82 or 35.9%) having a score of 0. Patients with a score of 3 or more and testing positive for COVID-19 were immediately referred to a hospital having adequate facilities to prevent delays. There were 51 patients (16.7%) with positive rapid test results, and 21 patients (6.8%) with positive PCR tests. There were 4 (1.3%) COVID-19 positive HCW. Conclusions Despite COVID-19 being a new threat, we have shown that developing an effective perioperative clinical pathway could eventually optimize healthcare worker safety.